The frequency of precocious segregation of sister chromatids in mouse female meiosis I is affected by genetic background - Danylevska, Anna; Kovacovicova, Kristina; Awadova, Thuraya; Anger, Martin (Chromosome research, 2014)
Mammalian female gametes frequently suffer from numerical chromosomal aberrations, the main cause of miscarriages and severe developmental defects. The underlying mechanisms responsible for the development of aneuploidy in oocytes are still not completely understood and remain a subject of extensive research. From studies focused on prevalence of aneuploidy in mouse oocytes, it has become obvious that reported rates of aneuploidy are strongly dependent on the method used for chromosome counting. In addition, it seems likely that differences between mouse strains could influence the frequency of aneuploidy as well; however, up till now, such a comparison has not been available. Therefore, in our study, we measured the levels of aneuploidy which has resulted from missegregation in meiosis I, in oocytes of three commonly used mouse strains-CD-1, C3H/HeJ, and C57BL/6. Our results revealed that, although the overall chromosomal numerical aberration rates were similar in all three strains, a different number of oocytes in each strain contained prematurely segregated sister chromatids (PSSC). This indicates that a predisposition for this type of chromosome segregation error in oocyte meiosis I is dependent on genetic background.
Keywords: Cell Count; chromatidy; oocyty; Mice, Inbred C3H; Polar Bodies; Meiosis; počet buněk; myši inbrední C3H; Chromatids; meióza; aneuploidie; segregace chromozomů; Animals; ženské pohlaví; Aneuploidy; zvířata; myši inbrední C57BL; myši; polární tělísko; Mice, Inbred C57BL; Chromosome Segregation; Mice; Female; Oocytes